Advanced age is not a barrier to chronic intracortical single-unit recording in rat cortex - Nolta, Nicholas F.; Christensen, Michael B.; Tresco, Patrick A. (Frontiers in Neuroscience, 2024)
Available evidence suggests that as we age, our brain and immune system undergo changes that increase our susceptibility to injury, inflammation, and neurodegeneration. Since a significant portion of the potential patients treated with a microelectrode-based implant may be older, we studied the chronic recording performance and the foreign body response (FBR) to a clinically used microelectrode array implanted in the cortex of 18 month old Sprague Dawley rats. To the best of our knowledge, this is the first preclinical study of its type in the older mammalian brain. Here, we show that single-unit recording performance was initially robust then gradually declined over a 12-week period, similar to what has been previously reported using younger adult rats and in clinical trials. In addition, we show that FBR biomarker distribution was similar to what has been previously described for younger adult rats implanted with multi-shank recording arrays in the motor cortex. Using a quantitative immunohistochemcal approach, we observed that the extent of astrogliosis and tissue loss near the recording zone was inversely related to recording performance. A comparison of recording performance with a younger cohort supports the notion that aging, in and of itself, is not a limiting factor for the clinical use of penetrating microelectrode recording arrays for the treatment of certain CNS disorders.